Influence of fluctuating environmental factors on phytochemical changes in eggplant and cucumber during postharvest storage - Cortbaoui , Patrick E; Ngadi , Michael O (Journal of Postharvest Technology, 2018)
In tropical countries, fresh vegetables travelling from “farm-to-fork” are continuously exposed to different temperatures and solar radiation levels that seriously affect their phytochemical composition and consequently, their overall postharvest quality. Phytochemicals in plants are known for their valuable antioxidants and potential anti-inflammatory, and anti-cancer benefits. In this work, freshly harvested eggplants and cucumbers were stored for 10 days in controlled chambers with varied combinations of temperature and light. Crude extracts of freeze-dried produce were used to determine the total phenolic contents (TPC) using the Folin-Ciocalteau method, then these reactions were monitored spectrophotometrically. Phytochemical changes were quantified over time using kinetic models. . Exposing vegetables to elevated temperatures (30oC) and direct light was found to significantly degrade their TPC. However, a rise in TPC (P < 0.05) was observed when the crops were maintained at 10oC in the absence of light. Moreover, storage at fluctuating environmental conditions was found to be the main contributor of the phenolic degradation in fresh eggplant (49.7% loss) and cucumber (83.8% loss). This study was useful in advancing knowledge on characterizing postharvest quality loss of fresh commodities from the perspective of health attributes rather than conventional sensory parameters, and aiming to effectively quantify postharvest losses in a more holistic manner.